Flow propensities in biological vessels and valves - Nzerem*†, F.E.; Ugorji*, H.C. (International Journal of Mathematical Analysis and Modelling, 2023)
Flows through the vascular appurtenances and biological valves are in a deep sense analogous to those obtained in other pipes and valves of similar configuration. However, the pulsatile nature of the cardiovascular flow, and the intrinsic coherent perturbation associated with the physiological and anatomical complications that reside in the biological structures, precisely the arteries and veins, and the heart valves, strike a remarkable distinction between them. The flow through the vascular structures was treated as a cylindrical pipe flow with characteristic coherent perturbation; the sound associated with or resulting from flow was considered, and the relationship between pressure and flow in open heart valves was treated, all of which were presented with the relevant equations. The equation involving the open heart valves is as good as furnishing the volume of blood in a physiological transmitral flow.